Pulmonary Arterial Hypertension in Adult-Onset Still’s Disease: Rapid Response to Anakinra - Marc Campos; Elena Schiopu (Case Reports in Rheumatology)
Adult-onset Still’s disease (AOSD) is a rare inflammatory condition characterized by spiking quotidian fever, rash, chronic arthralgia, leukocytosis, and occasional pulmonary involvement such as pleural effusion and transient pulmonary infiltrates. Pulmonary arterial hypertension (PAH) is a rare pulmonary complication of AOSD, and we are aware of only 5 cases reported in the literature. We report the case of a 27-year-old woman of Middle Eastern descent, with a 7-year history of AOSD, who developed severe pulmonary arterial hypertension (PAH). After unsuccessful exposure to various immunosuppressive regimens, shortly following the initiation of anakinra, an interleukin-1 (IL-1) receptor antagonist, her disease became quiescent and the PAH resolved. With this case report, we hope to show that anakinra, either by virtue of controlling the overall inflammation in AOSD, or by direct effect on the pulmonary microangiopathy, can improve severe PAH.